Finger reach envelope using the marching cubes method. (8th November 2010) - Johnson, Ross; Yang, Jingzhou; Long, James
Reach envelope is commonly used not only to evaluate hand function but also to assess joysticks, tools for ergonomic design. A digital human simulation suite has been developed recently which includes customised hand model, kinematics, grasping, discomfort assessment, finger posture prediction, biomechanics, etc. The reach envelope is one of the hand capabilities in this hand simulation suite. This paper mainly focuses on the digital hand model and the procedure for implementing the marching cube method for generating finger and hand reach envelopes. The digital hand model has 25 degrees of freedom (DOF) and can realistically simulate all possible movements of each finger in three-dimensional space. The method involves the following steps: 1) select an end-effector (point of interest); 2) select DOFs to freeze; 3) choose scalar field resolution; 4) generate point cloud; 5) generate 3D scalar field; 6) generate mesh. The marching cubes method for reach envelope is much faster than other methods presented in the literature. The developed package can be used to generate the reach envelope for any point on any finger.